Objectively Measured Physical Activity and Sedentary Time Among Adults With and Without Stroke: A National Cohort Study. Issue 11 (27th September 2021) - Duran, Andrea T.; Pascual, Christian B.; Goldsmith, Jeff; Howard, Virginia J.; Hutto, Brent; Colabianchi, Natalie; Vena, John E.; McDonnell, Michelle N.; Blair, Steven N.; Hooker, Steven P.; Diaz, Keith M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: We examined differences in the volume and pattern of physical activity (PA) and sedentary behavior between adults with and without stroke. Methods: We studied cohort members with an adjudicated or self-reported stroke (n=401) and age-, sex-, race-, region of residence-, and body mass index-matched participants without a history of stroke (n=1203) from the REGARDS study (Reasons for Geographic and Racial Differences in Stroke). Sedentary behavior (total volume and bouts), light-intensity PA, and moderate-to-vigorous-intensity PA were objectively measured for 7 days via hip-worn accelerometer. Results: Sedentary time (790.5±80.4 versus 752.4±81.9 min/d) and mean sedentary bout duration (15.7±12.6 versus 11.9±8.1 min/d) were higher and PA (light-intensity PA: 160.5±74.6 versus 192.9±73.5 min/d and moderate-to-vigorous-intensity PA: 9.0±11.9 versus 14.7±17.0 min/d) lower for stroke survivors compared with controls ( P <0.001). Stroke survivors also accrued fewer activity breaks (65.5±21.9 versus 73.31±18.9 breaks/d) that were shorter (2.4±0.7 versus 2.7±0.8 minutes) and lower in intensity (188.4±60.8 versus 217.9±72.2 counts per minute) than controls ( P <0.001). Conclusions: Stroke survivors accrued a lower volume of PA, higher volume of sedentary time, and exhibited accrual patterns of more prolonged sedentary bouts and shorter, lower intensity activity breaks compared with persons without stroke.